2021
DOI: 10.1002/jgc4.1513
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of genetic counseling and multi‐gene panel testing among women in the Intermountain West with previous negative BRCA1 and BRCA2 results contacted for updated testing

Abstract: Women with a personal history of breast or ovarian cancer who previously had BRCA1/2 testing now have the opportunity for additional genetic risk information through multi-gene panel testing. However, little is known about women's receptivity to further contact and uptake of genetic counseling and updated genetic testing.Utilizing a clinic database to identify potential participants, we prospectively contacted women in the United States with a personal and/or family history of breast or ovarian cancer who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Further, in Hampel's 2009 commentary, despite being able to identify which patients would potentially benefit, the Ohio State University Cancer Center only initially tested 12 of the 319 patients who were mailed letters regarding the availability of BRCA1/2 deletion/duplication analysis (Hampel, 2009). Other studies showed similar difficulties with revisiting genetic testing (Mooney et al, 2021; Romero Arenas et al, 2018; Sawyer et al, 2019).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Further, in Hampel's 2009 commentary, despite being able to identify which patients would potentially benefit, the Ohio State University Cancer Center only initially tested 12 of the 319 patients who were mailed letters regarding the availability of BRCA1/2 deletion/duplication analysis (Hampel, 2009). Other studies showed similar difficulties with revisiting genetic testing (Mooney et al, 2021; Romero Arenas et al, 2018; Sawyer et al, 2019).…”
Section: Discussionmentioning
confidence: 67%
“…(Hampel, 2009). Other studies showed similar difficulties with revisiting genetic testing (Mooney et al, 2021;Romero Arenas et al, 2018;Sawyer et al, 2019).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations